2020
DOI: 10.1101/2020.10.25.20219063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence and spread of a SARS-CoV-2 variant through Europe in the summer of 2020

Abstract: A variant of SARS-CoV-2 emerged in early summer 2020, presumably in Spain, and has since spread to multiple European countries. The variant was first observed in Spain in June and has been at frequencies above 40% since July. Outside of Spain, the frequency of this variant has increased from very low values prior to 15th July to 40-70% in Switzerland, Ireland, and the United Kingdom in September. It is also prevalent in Norway, Latvia, the Netherlands, and France. Little can be said about other European countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
405
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(430 citation statements)
references
References 52 publications
17
405
3
5
Order By: Relevance
“…More patients were admitted during the second wave, they were younger and there were fewer deaths, in agreement with results reported by previous research in several countries [2,3,12]. The reasons for the clear differences between the two periods are not yet known although it has been suggested that a new variant of SARS-CoV-2 emerged in early summer 2020 in Spain [9], a variant that was linked to outbreaks among young agricultural workers in the north-east of the country. Transmission to the general population in that area was then replicated across the country.…”
Section: Discussionsupporting
confidence: 89%
“…More patients were admitted during the second wave, they were younger and there were fewer deaths, in agreement with results reported by previous research in several countries [2,3,12]. The reasons for the clear differences between the two periods are not yet known although it has been suggested that a new variant of SARS-CoV-2 emerged in early summer 2020 in Spain [9], a variant that was linked to outbreaks among young agricultural workers in the north-east of the country. Transmission to the general population in that area was then replicated across the country.…”
Section: Discussionsupporting
confidence: 89%
“…From the Costa Rican sequenced cases, none harbors yet this mutation. Also, a European cluster (called 20A.EU1) has been reported with a significant spread in summer 2020, mainly in Spain (Hodcroft et al, 2020). Genome sequences in this group have at least six variants, including the mutation A222V in the Spike protein and A220V in the nucleoprotein.…”
Section: Other Variantsmentioning
confidence: 99%
“…Genetic diversity of SARS-CoV-2 genomes has demonstrated a large number of independent introductions of the virus into many countries of the world but China (van Dorp et al, 2020). Although strong relationships between specific variants or clades in SARS-CoV-2 and the clinical outcome have not been identified (Grubaugh, Hanage, & Rasmussen, 2020;Hodcroft et al, 2020;van Dorp et al, 2020), different relevant parameters could be impacted by mutations in the virus genome. These include transmissibility, severity, clinical management, mortality, vaccines as well as the performance of molecular tests for diagnosis (Hodcroft et al, 2020;Koyama, Platt, & Parida, 2020;Teng, Sobitan, Rhoades, Liu, & Tang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation confers increased infectivity on the virus (37) and was readily generated in sufficient numbers to ensure its expansion. As of this writing, a second selective sweep appears to be underway in Europe, with the 2A.EU1 variant (38).…”
Section: Discussionmentioning
confidence: 92%